Main Directions of Protection of Equipment and Pipelines Against Biocorrosion - Gurbanov, A.N. (Herald of Azerbaijan Engineering Academy, 2021)
The problems of biocorrosion and damage to the outer and inner surfaces of pipelines and systems in the oil and gas industry are considered. The main factors influencing the development of biocorrosion are revealed, conditions favorable for the reproduction of microorganisms are established under the insulating material. The results of research of inhibitors for applying with insulating materials for pipelines, in particular, bituminous mastics, are presented. Based on a comparative analysis of existing methods for detecting and protecting biocorrosion, the main directions of control and protection of equipment against biocorrosion are determined. It is shown that monitoring and control of the state of pipelines in real time is one of the promising areas of protection against biocorrosion.